2007
DOI: 10.1111/j.1365-2435.2007.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of a freshwater clam along an abiotic gradient: too much oxygen may limit distribution

Abstract: Summary1. Distribution and abundance patterns are influenced by cellular responses to abiotic stressors. 2. The freshwater clam Sphaerium sp. inhabits swamp/stream systems in Uganda, in which dissolved O 2 (DO), pH and water transparency form ecotonal gradients along tributary streams. Along a swamp/stream transect, clam abundance was negatively related to DO, pH and transparency; clams were most abundant in the hypoxic/acidic swamp, less abundant in the ecotone, and absent from stream sites (neutral pH and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
(92 reference statements)
3
16
0
Order By: Relevance
“…We found that steady state levels of RNA oxidation in G. dibranchiata increased significantly with in vitro and in vivo sulfide exposure. In all cases, RNA oxidation was greater than DNA oxidation, which is consistent with the findings of previous studies (Hofer et al 2005, 2006; Joyner-Matos et al 2007). Interestingly, we also found that RNA oxidation was correlated with DNA oxidation in coelomocytes but not in the body wall tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that steady state levels of RNA oxidation in G. dibranchiata increased significantly with in vitro and in vivo sulfide exposure. In all cases, RNA oxidation was greater than DNA oxidation, which is consistent with the findings of previous studies (Hofer et al 2005, 2006; Joyner-Matos et al 2007). Interestingly, we also found that RNA oxidation was correlated with DNA oxidation in coelomocytes but not in the body wall tissue.…”
Section: Discussionsupporting
confidence: 92%
“…In the only measurement of 8-oxoGuo in a wild population of animals to date, there was a positive correlation between environmental dissolved O 2 concentration and RNA oxidation in a hypoxia-tolerant bivalve (Joyner-Matos et al 2007). RNA oxidation has otherwise not been extensively studied outside of its key role in Alzheimer’s disease (e.g., Nunomura et al 1999) and Parkinson’s disease (e.g., Zhang et al 1999) and its tendency to increase with age in mammals (Hofer et al 2005, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, marine environments vary widely in thermal characteristics, partial pressure of oxygen, degree of pollution and light environment, all of which can influence the degree of oxidative insult experienced by an individual, and many marine organisms adjust their AO systems in response to this environmental variability to maintain a stable redox state (reviewed in Lesser 2006; Buttemer, Adele & Costantini 2010). Furthermore, within species, population densities can vary with habitat and, at least in freshwater clams ( Sphaerium sp), some of this variation has been tied to OD; clams were most abundant and showed lower levels of nucleic acid damage in relatively more hypoxic environments (Joyner‐Matos et al. 2007).…”
Section: Ecological and Evolutionary Issues Of Osmentioning
confidence: 99%
“…However, sulfide may also have antioxidant properties: H 2 S can directly scavenge reactive oxygen and nitrogen species (Whiteman et al, 2004;Whiteman et al, 2005), and reduce lipid peroxidation in a mouse model of hepatic ischemiareperfusion injury (Jha et al, 2008). Nonetheless, oxidative stress is increased in at least some marine organisms during sulfide exposure (Abele-Oeschger and Oeschger, 1995;Joyner-Matos et al, 2007;Julian et al, 2005;Tapley, 1993), as well as in mammalian cells exposed to sulfide in vitro (Attene-Ramos et al, 2007;Eghbal et al, 2004). Furthermore, environmental conditions other than sulfide, in particular high concentrations of dissolved metals, may contribute to oxidative stress at hydrothermal vents (Bebianno et al, 2005).…”
Section: Introductionmentioning
confidence: 99%